KEBIJAKAN DAN TANGGUNG JAWAB PEMERINTAH DALAM MEWUJUDKAN PERLINDUNGAN DAN PENGELOLAAN SUMBER DAYA ALAM BAGI MASA MENDATANG - Nur Asnah (Pelantar Press, 2023)
Environmental problems are increasingly showing an increase. This indicates that environmental policies have not been successful. Exploitation of natural resources and the environment has led to a worsening of the environmental quality of natural resources, particularly in terms of monitoring and developing living mechanisms. Environmental protection and management based on Article 1 point (2) of Law Number 32 of 2009 concerning Environmental Protection and Management (UUPPLH) is a systematic and integrated effort made to preserve environmental functions and prevent environmental pollution and/or damage that includes planning, utilization, control, maintenance, supervision, and law enforcement. Given the complexity of environmental protection and management and the problems that are cross-sectoral and regional in nature, in the implementation of development it is necessary to plan and implement environmental protection and management that are in line with the principles of sustainable development, namely balanced economic, socio-cultural and environmental development as the pillars interdependent and mutually reinforcing one another. In its implementation it involves various parties, as well as strictness in complying with environmental law. It is hoped that with the participation of various parties and supervision and compliance with laws that can really be enforced, it can be used as a common reference for managing the environment in a wise way so that the goals of sustainable development can really be implemented in the field and not stop at mere slogans.